Elevated Small Nuclear Ribonucleoprotein Polypeptide an Expression Correlated With Poor Prognosis and Immune Infiltrates in Patients With Hepatocellular Carcinoma - Zhang, Youfu; Wang, Xuyang; Wang, Huaxiang; Jiang, Yi; Xu, Zhidan; Luo, Laibang (Frontiers in Oncology, 2022)
Background: Elevated Small Nuclear Ribonucleoprotein Polypeptide A (SNRPA) can enhance tumor cell growth and proliferation in various cancers. However, rarely studies focus on the comprehensive analysis of SNRPA in hepatocellular carcinoma (HCC). Methods: TCGA and GEO databases were used to analyze the mRNA expression of SNRPA in HCC. Protein expression of SNAPA was validated using immunohistochemistry. Stably transfected HCC cells were used to investigate the role of SNRPA in the progression of HCC. The functional enrichment analysis was utilized for the biological function prediction. The CIBERSORT and ssGSEA algorithm were used to evaluate the composition of the tumor microenvironment and immunocyte infiltration ratio. Results: The SNRPA expression was upregulated in HCC and positively correlated with tumor stage and grade. SNRPA overexpression were independent risk factors for poor overall survival (OS) and recurrence-free survival (RFS). In patients with early-stage disease, low alpha-fetoprotein expression, and better differentiation, SNRPA still exhibited the excellent prognostic value. Knockdown of SNRPA inhibited the proliferation and migration while promoting the apoptosis of HCC cells. Higher methylation of the CpG site cg16596691 correlated with longer OS in HCC patients. Genes co-expressed with SNRPA were overexpressed in HCC and correlated with shorter OS. The GO and KEGG enrichment analysis showed that SNRPA expression was related to mRNA splicing, spliceosome signaling. GSEA demonstrated that the main enrichment pathway of SNRPA-related differential genes was spliceosome signaling, cell cycle signaling, P53 signaling pathway, T cell receptor signaling pathway, natural killer cell-mediated signaling. CIBERSORT and ssGSEA algorithm revealed that SNRPA was mainly associated with the higher proportion of CD8+T cells, T cells follicular helper, T cells regulatory, Macrophages M0, and the lower proportion of T cells CD4 memory resting, NK cells resting, Monocytes, and Mast cells resting. Conclusion: Elevated SNRPA enhances tumor cell proliferation and correlated with poor prognosis and immune infiltrates in patients with HCC.